Penerapan Pembuatan Sampel Uji Tarik FCD Type Y-Blok Spesimen pada PT. Aneka Adhilogam Karya Klaten - Iqbal Zulfikar Alief Utama; Lutiyatmi; Akhmad Nurdin (CV. Multi Kreasi Media, 2025)
The metal casting process can be briefly interpreted as a sequence of processes for making cast objects that are mutually continuous, starting from the design of the cast object to the final processing process. The Ceper metal casting industry is also a metal casting industry that carries out the casting process, one type of cast product is a product from cast iron with the type of nodular cast iron (FCD) and consumers who order this FCD product come from various groups, both private institutions and government institutions, even internationally. Consumers want the ordered product to be good and high quality, to meet these consumer demands, the metal casting industry that produces products must have their products tested and maintained for quality both in terms of manufacturing and testing. FCD products made in the Ceper metal casting industry, most of the product results and their testing have not been able to meet the standard FCD criteria. The results of supporting tests to determine the type of FCD product include the FCD product manufacturing process, chemical composition tests, hardness, metallography, thermocouples and tensile strength of the products made. The purpose of this study is to obtain quality nodular cast iron (FCD) casting products according to the needs of the Ceper metal casting industry and can reduce the reject ratio of cast products. This community service program was conducted to implement the production of nodular cast iron samples in partner industries, and to conduct the testing process along with the creation of standard samples. Molds for tensile test samples were created and further research was conducted on the method for producing Y-Block Tensile Test Specimens.